The Effects of the Speakers’ Emotions on the Use of Implicatures in Political Discourse (A Psycho-Pragmatic Study) - Yusri Yusri (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. This study aims to discover how emotions influence speakers on the use of implicatures. The research was qualitative, using a psycho-pragmatic approach. The data were in the form of public comments about political discourse posted on the comment column of an online daily newspaper called Kompas. Data collection was performed using documentation techniques. The results show that public comments tend to contain conventional implicatures. Based on these results, it can be seen that there is a relationship between negative emotions in the form of anger or irritation and the selection of conventional implicatures. Speakers who have negative emotions tend to use conventional implicatures more frequently than unconventional implicatures in their utterances.